J15 Exploring the use of music during ultramarathons using a think-aloud procedure - Bozianu, Dominic; Jones, Leighton (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Introduction: ultrarunning is a rapidly growing sport and is receiving increased attention in scientific literature. Ultrarunning is the act of running ultramarathons, defined as any distance over a marathon (42.2 km). Some ultramarathons are run over a set time e.g., 12 hours. Ultrarunners face many different challenges throughout their races, including injuries and pain, thoughts of quitting, and boredom (Holt et al., 2014, Sport Psych, 28, 22-35). The application of music during sports and exercise has been shown to be a powerful psychological and ergogenic aid, however, there is a dearth of studies exploring how music is applied in ultrarunning. Previous research around ultramarathons has typically used interviews or a range of scales to collect data (Watkins et al., 2022, Psych Sport Ex, 63, 102271). Think-Aloud (TA) procedures have been used in studies involving shorter distance running (Johnson et al., 2023, Int J Sport Ex Psych) but have not yet been applied to ultrarunning. Accordingly, the present study uses a TA approach to capture ultramarathoners’ thoughts and feelings during an event where they listen to music. Method: ten participants completed a two-stage training procedure of TA to conform with established procedures (McGreary et al., 2024, Sport Ex Perf Psych). The TA procedure permits recording of real-time thoughts. The first stage consists of two problems: a multiplication problem, and an anagram-based problem. The second stage involves thinking aloud for a short period while on a training run. Following the training, participants recorded their thoughts at six time points around their event: before the race, after 1 mile, at 30, 60, and 90% into the race, and within five minutes of race completion. Data Analysis: thematic analysis will be undertaken on the transcribed data and will follow standard procedures. Applications: TA has not been applied in ultrarunning previously and its use in the present study can offer evidence to its future feasibility for similar research. Findings of this study will inform the practical application of music around ultramarathon events, with insights offered for athletes and coaches. Moreover, recommendations will be made as to when music could be applied during an event to maximise its effects. These findings will be couched within contemporary conceptual frameworks for applying music in sport and exercise contexts and offer fresh insight into how these models could be expanded to consider ultra-endurance events more fully.